Self-preserving gelatin emulgel containing whole cell probiotic for topical use: preclinical safety, efficacy, and germination studies. (2nd November 2021) - Sharma, Garima; Sharma, Manuhaar; Sood, Rishav; Neelamraju, Jayanthi; Lakshmi, Suvarna G.; Madempudi, Ratna Sudha; Rishi, Praveen; Kaur, Indu Pal
ABSTRACT: Background: Dermal disorders, owing to disruption of skin-microflora balance can be served by direct application of probiotics. However, there are few topical whole probiotic products in market because of (i) loss of viability during manufacturing and storage(ii) inadequate germination and retention on skin. Presently we report a novel (IPA 201811010395) emulgel incorporating Bacillus coagulans (Unique IS-2) for possible topical use. Methods: Developed emulgel was characterized for particle size, texture, rheology, morphology, water activity, self-preservation, safety, and stability. Results: We successfully incorporated 97 ± 5% (1.7×10 8 CFU/g) Bacillus coagulans in honeycomb network of gelatin nanoparticles (≈ 600 nm). Maintenance of CFU at 30 ± 2°C, 65 ± 5% RH for 3 months confirmed viability of incorporated probiotic. Low water-activity (0.66–0.732aw ) and challenge test (0.05–0.5% viability) confirmed its self-preserving nature. Early initiation (6 h) and complete (24 h) spore germination was evident onrabbit skin. No cytotoxicity, dermal irritation or translocation established its safety. Faster wound closure and reduced oxidative stress (LPO, catalase, SOD, glutathione reductase) in comparison to Soframycin® (1%w/w Framycetin) was observed in excision wound in mice. Conclusions: A whole cell probiotic formulation that is self-preserving, maintains probiotic viability, guarantees germination, and has wound healing properties was successfully formulated.